Application of posture, breathing and warm up techniques in singing / Siti Hanis Hassan - Hassan, Siti Hanis (Faculty of Music, 2016)
This case study investigated application of posture, breathing and warm-ups techniques in singing. A good application on vocal techniques are believe to contribute the correct techniques in singing and can sing with beautifully. Many vocal students did not applying correct techniques in singing. The goal of this current study was to describe students understanding of posture and breathing techniques in singing and use of warmup exercises during perfomance. Other than that to identify the problems faced in applying the techniques during perfomance among vocal students at UiTM and to investigate the different problems faced in applying the techniques during perfomance between genders among students in UiTM. To achieve this, data has been collected from vocal students in UiTM which is seventy nine participants completed the survey. Participants included voice students from Diploma and Degree from four departments which is Music Education, Music Perfomance, Music Composition and Music Bussiness.